Monitoring brain neuronal activity with manipulation of cardiac events in a freely moving rat. (November 2018) - Shikano, Yu; Ikegaya, Yuji; Sasaki, Takuya
Highlights: Our method records brain electrical signals, electroencephalogram, electromyogram. The recording can be combined with stimulation of peripheral organs. The simulation includes cardiac muscle stimulation or a conventional VNS system. This method will uncover neurophysiological correlates of mind-body associations. Abstract: Behavioral and cognitive studies have demonstrated that brain functions are affected by the activity states of the peripheral organs, such as the cardiac and respiratory systems. However, detailed neurophysiological mechanisms underlying the body-brain interactions remain unknown. In this study, we developed a method for manipulating activity levels of the heart using direct cardiac stimulation and vagus nerve stimulation that can be combined with recording cerebral local field potentials using a microdrive system, electrocardiograms, electromyograms, in a freely moving rat. With this method, the electrical stimulation to the heart increases heart rates up to 14 Hz, whereas the vagus nerve stimulation decreases heart rates to 3 Hz. Transient electrical artifacts arising from the peripheral stimulation are not contaminated in cortical local field potential signals low-pass filtered at 150 Hz and distinguishable from extracellular multiunit signals. The technique will contribute to understanding the neurophysiological correlate of mind-body associations in health and disease.